2020
DOI: 10.1111/ncn3.12420
|View full text |Cite
|
Sign up to set email alerts
|

Case report of myelin oligodendrocyte glycoprotein antibody‐positive encephalitis mimicking hemiplegic migraine

Abstract: Even though symptoms are important in the diagnosis of hemiplegic migraine, myelin oligodendrocyte glycoprotein antibody‐positive benign unilateral cortical encephalitis shows unique progress and findings on magnetic resonance imaging. We encountered a case of hemiplegic migraine showing cortical hyperintensity on magnetic resonance imaging, and positive results for myelin oligodendrocyte glycoprotein antibody. A certain proportion of patients diagnosed with hemiplegic migraine appear to show myelin oligodendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Therefore, we speculated that the lesions of the cortex are involved in vascular distribution. Reviewing the cases in our study, we observed that in the 11 patients who underwent cerebrovascular perfusion tests, including MRI, arterial spin labelling imaging, and single-photon emission computed tomography, 10 patients displayed vasodilation of the cerebrovascular branch, indicating high cerebrovascular perfusion ( Ogawa et al, 2017 ; Ikeda et al, 2018 ; Fujimori et al, 2020b ; Katsuse et al, 2020 ; Matoba et al, 2020 ; Otani et al, 2020 ; Jain et al, 2021 ; Nie et al, 2021 ), which usually can be completely restored to normal after steroid therapy. Although there is no clear conclusion about the relationship between vascular distribution and lesions, we speculate that peripheral vessels of the middle cerebral artery or anterior cerebral artery may also be involved in the pathogenesis of the disease after cortical inflammation occurs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, we speculated that the lesions of the cortex are involved in vascular distribution. Reviewing the cases in our study, we observed that in the 11 patients who underwent cerebrovascular perfusion tests, including MRI, arterial spin labelling imaging, and single-photon emission computed tomography, 10 patients displayed vasodilation of the cerebrovascular branch, indicating high cerebrovascular perfusion ( Ogawa et al, 2017 ; Ikeda et al, 2018 ; Fujimori et al, 2020b ; Katsuse et al, 2020 ; Matoba et al, 2020 ; Otani et al, 2020 ; Jain et al, 2021 ; Nie et al, 2021 ), which usually can be completely restored to normal after steroid therapy. Although there is no clear conclusion about the relationship between vascular distribution and lesions, we speculate that peripheral vessels of the middle cerebral artery or anterior cerebral artery may also be involved in the pathogenesis of the disease after cortical inflammation occurs.…”
Section: Discussionmentioning
confidence: 78%
“…We finally obtained 33 cases from 25 articles and combined with our two cases, a total of 35 cases were reviewed systematically ( Ogawa et al, 2017 ; Hamid et al, 2018 ; Ikeda et al, 2018 ; Budhram et al, 2019 , 2020 ; Haddad et al, 2019 ; Patterson et al, 2019 ; Fujimori et al, 2020b ; Hochmeister et al, 2020 ; Katsuse et al, 2020 ; Matoba et al, 2020 ; Otani et al, 2020 ; Russ et al, 2020 ; Takamatsu et al, 2020 ; Tao et al, 2020 ; Ahsan et al, 2021 ; Chang et al, 2021 ; Doig et al, 2021 ; Jain et al, 2021 ; Kim et al, 2021 ; Maniscalco et al, 2021 ; Nie et al, 2021 ; Stamenova et al, 2021 ; Tian et al, 2021 ; Wang et al, 2021 ; Table 1 ). The main demographic data, clinical characteristics, laboratory results, and imaging results are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…1 Jasmine Ashhurst, 2 Rami Haddad, 3 Rob Zielinski. 1 Case Report Lambert-Eaton Myasthenic Syndrome (LEMS) is a neuromuscular disorder caused by antibodies directed to the presynaptic voltage-gated calcium channel.…”
Section: Pembrolizumab Induced Lambert-eaton Myasthenic Syndromementioning
confidence: 99%
“…Introduction Rare cases of double positive Epstein-Barr virus (EBV) and anti-N-methyl-D-aspartate receptor (anti-NMDAR) antibody causing encephalitis have been described associated with solid organ transplant. [1][2][3][4] Opsoclonus-myoclonus syndrome is often a paraneoplastic or parainfectious phenomenon, but has only rarely been described associated with anti-NMDAR and usually with additional neuropsychiatric symptoms or encephalopathy. [5][6] We describe the rare case of a renal transplant patient with opsoclonus-myoclonus syndrome…”
Section: Ebv and Nmda Receptor Antibody Positive Opsoclonus-myoclonus Syndrome In An Immunocompromised Patient With Renal Clear Cell Carcmentioning
confidence: 99%
See 1 more Smart Citation